2007
DOI: 10.1111/j.1399-0012.2007.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplant outcome in high‐cardiovascular risk recipients

Abstract: Post-transplant survival of high-CV risk patients (with known CAD) is lower than that of low-risk recipients but remains acceptable. Cardiac interventions may reduce perioperative risk but do not reduce the probability of post-transplant cardiac events to that of low-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…16 Diffuse atherosclerosis and microvascular dysfunction may partially explain why the association between elevated LDL cholesterol and myocardial infarction is attenuated in patients with advanced CKD 17 and may also help us understand previously observed discrepancies between traditional cardiovascular risk assessment and outcomes after renal transplantation. 18 Additional studies are needed to determine whether longitudinal improvement in global CFR is associated with risk reduction. If that can be shown, it may be appropriate to use global CFR as a surrogate for mortality in future clinical trials involving patients with dd-ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…16 Diffuse atherosclerosis and microvascular dysfunction may partially explain why the association between elevated LDL cholesterol and myocardial infarction is attenuated in patients with advanced CKD 17 and may also help us understand previously observed discrepancies between traditional cardiovascular risk assessment and outcomes after renal transplantation. 18 Additional studies are needed to determine whether longitudinal improvement in global CFR is associated with risk reduction. If that can be shown, it may be appropriate to use global CFR as a surrogate for mortality in future clinical trials involving patients with dd-ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Jeloka et al 35 retrospectively classified 429 renal transplant recipients as high cardiovascular risk (nϭ61) and low cardiovascular risk (nϭ368). The high-risk group included patients with a history of angina, MI, or significant CAD found on cardiac catheterization.…”
Section: What Are the Goals Of Preoperative Cardiac Risk Evaluation Imentioning
confidence: 99%
“…This finding suggested that significant CAD was a predictor of future cardiovascular events [18]. In another study, post-transplantation cardiac events and survival were reported to be 31.3% and 82.8% in high-risk patients, whereas it was 6.5% and 93.1% in low risk patients [19]. However, the study by Gowdak et al showed that in the overall population for each 100 CAG performed, there would be 55 patients with no significant CAD and 10 cardiovascular events associated with it [18].…”
Section: Epidemiologymentioning
confidence: 95%